Editorial - Magalhães, Izabel (Cadernos de Linguagem e Sociedade, 2010)
In this number of Papers on Language and Society, we are beginning a new stage which can be defined as follows: 1) a clear editorial policy, characterised by the study of language as text and social practice (discourse) in a critical perspective; 2) multilingualism, including Portuguese, English, Spanish and French; 3) a language policy which is contrary to prejudice or any kind of discrimination. We also discuss briefly the codification of ‘man’ and ‘woman’ in the Aurélio Portuguese dictionary. It shows that the dictionary constructs a positive view of men and a rather negative view of women. We also suggest that the same thing happens in the codificaton of ethnic minorities. These are some of the issues we propose to discuss in this journal.